36-2a=-8(a-6)

Simple and best practice solution for 36-2a=-8(a-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 36-2a=-8(a-6) equation:



36-2a=-8(a-6)
We move all terms to the left:
36-2a-(-8(a-6))=0
We calculate terms in parentheses: -(-8(a-6)), so:
-8(a-6)
We multiply parentheses
-8a+48
Back to the equation:
-(-8a+48)
We get rid of parentheses
-2a+8a-48+36=0
We add all the numbers together, and all the variables
6a-12=0
We move all terms containing a to the left, all other terms to the right
6a=12
a=12/6
a=2

See similar equations:

| 13-7x=10x+3 | | 144x+20+7x=48 | | (3x-60)=120 | | 7s-2s-6=14 | | x/3+4x/6=12/3 | | (3p-4)-(5p+3)=5 | | 27k=297 | | 9=y-0.55 | | r-6/4=2 | | -3+2x=x+8 | | -4j+2=-2(-1+2j) | | -8(3n+2)+4(5n+8)=-n-5n | | 5-4a=-15 | | 4h+6=3h | | 8v-22=42 | | 2/3x+-9=3 | | 8-4k=-96 | | 2.5m=12.5 | | 9n-7n-(-7)=-15 | | 15n+3=12 | | 7x+3(2x-2)=6(1+x) | | 5x+3+(x+4)=28 | | 1/2(2x+12)=3x | | 3+x=6/x-2 | | 3(x+2)=2x+12 | | -7(2k+3)=3k | | 4b/7+5=13 | | 6y-9y=4=2y-2 | | 29=2(x-4)+1 | | 100=10x10= | | 2w+8=-3+3w | | -27+5b=5(b-4) |

Equations solver categories